4x+5y=5 6x+7y=7

4x+5y=5

-10y-4x=-7

-10y-4x=-7

3X+5Y=5

Here is a solution:

Multiply the first equation with 3;

3(4x+10y)=3(2)

12x + 30y = 6------(A)

Now multiply the second equation with 4;

4(3x+5y)=4(5)

12x + 20y = 20------(B)

Now subtract (B) from (A), we get:

10y = -14

y = -1.4 , now put the value of y in any one equation to get the value of x:

12x + 20y = 20

12x + 20(-1.4) = 20

12x - 28 = 20

12x = 48

x = 4 and y = -1.4 is the solution

Multiply the first equation with 3;

3(4x+10y)=3(2)

12x + 30y = 6------(A)

Now multiply the second equation with 4;

4(3x+5y)=4(5)

12x + 20y = 20------(B)

Now subtract (B) from (A), we get:

10y = -14

y = -1.4 , now put the value of y in any one equation to get the value of x:

12x + 20y = 20

12x + 20(-1.4) = 20

12x - 28 = 20

12x = 48

x = 4 and y = -1.4 is the solution